A Study on the Meaning Construction of Digital Narrative Discourse of Learners of English in Universities: Taking Holiday-Themed Multimodal Videos as an Example - Wang, Xuan; Ji, Mengmeng (Education Insights, 2026)
Learner digital storytelling transforms given narrative content into dynamic multimedia works, a pedagogical approach which has demonstrated a highly positive impact on contemporary English language teaching. Drawing extensively on the Visual Grammar theoretical framework proposed by Kress and van Leeuwen (2020), this empirical study systematically examines foreign language videos published on the official WeChat account of a university located in Northwest China. It conducts a rigorous multimodal discourse analysis across three primary dimensions—representational meaning, interactive meaning, and compositional meaning—to comprehensively explore how university English learners construct complex discourse meaning specifically at the visual level. The analytical findings reveal three key insights: 1) At the level of representational meaning, the utilized images frequently lack sufficient narrative strength; 2) At the level of interactive meaning, the overall meaning construction tends heavily toward the objective transmission of factual information; 3) In terms of compositional meaning construction, visual salience is notably insufficient across the sampled media. Therefore, while the visual modality in the short videos created by these learners generally serves an adequate communicative function, it functions primarily as a supplementary tool to the dominant textual modality, meaning the holistic construction of visual meaning remains incomplete. By analyzing bilingual videos focused on traditional Chinese festivals, this study explores the nuanced characteristics of learners' multimodal expression, offering valuable pedagogical insights for language teachers. Furthermore, it helps learners gain a deeper understanding of Chinese history, customs, and cultural heritage, ultimately laying a robust foundation for effective cross-cultural dissemination.